Comparative Effect of Crude and Commercial Enzyme on the Juice Recovery from Bael Fruit (Aegle marmelos Correa) Using Principal Component Analysis - Anurag Singh; H. K. Sharma; Sanjay Kumar; Ashutosh Upadhyay; K. P. Mishra (International Journal of Food Science)
The effect of incubation time, incubation temperature, and crude enzyme concentration was observed on the yield, viscosity, and clarity of the juice obtained from bael fruit pulp. The recommended enzymatic treatment conditions from the study were incubation time 475 min, incubation temperature 45°C, and crude enzyme concentration 0.20 mL/25 g bael fruit pulp. The recovery, viscosity, and clarity of the juice under these conditions were 82.9%, 1.41 cps, and 21.32%T, respectively. The variables, clarity, and yield were found as principal components for comparing different samples of the juice treated with enzyme.